The dark side of the force: the military dictatorship and the history course of the National School of Philosophy of the University of Brazil (FNFi/UB) - Ferreira, Marieta de Moraes (História da Historiografia: International Journal of Theory and History of Historiography, 2013)
The aim of this article is to focus on the final years of the course of history at the FNFi/UB (1958-1968), in order to recover the political and historiographical conflicts that took place there, and to understand the trajectory of this disciplinary field and its professionalization-process at a moment of great transformations. The article’s coverage extends to the discussions related to the issues that characterize the memories of traumatic events and the History of the Present Time. Different types of sources were used, such as oral statements, newspapers, FNFi documents, and police archives.